Oral History Interview with Alma Ziegler, 1995 - Ziegler, Alma, interviewee; Coughlin, Kathleen E., interviewer (My University, 2009)
Alma Ziegler was a former member of the Milwaukee Chicks baseball team. This interview was conducted by Kathleen E. Coughlin as part of a 1995 oral history course at the University of Wisconsin-Milwaukee.
Keywords: All-American Girls Baseball League; Borchert Field (Milwaukee, Wis.); Milwaukee Chicks (Baseball Team); Women baseball players -- Wisconsin -- Milwaukee; World War, 1939-1945 -- Women -- Wisconsin -- Milwaukee